Elliptic flow of electrons from beauty-hadron decays in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; López, Jorge; Martin, Nicole Alice; Ohlson, Alice; et al. (Physical review letters, 2021)
The elliptic flow of electrons from beauty hadron decays at midrapidity (|y|<0.8) is measured in Pb-Pb collisions at √sNN=5.02 TeV with the ALICE detector at the LHC. The azimuthal distribution of the particles produced in the collisions can be parametrized with a Fourier expansion, in which the second harmonic coefficient represents the elliptic flow, v2. The v2 coefficient of electrons from beauty hadron decays is measured for the first time in the transverse momentum (pT) range 1.3-6 GeV/c in the centrality class 30%-50%. The measurement of electrons from beauty-hadron decays exploits their larger mean proper decay length cτ≈500 μm compared to that of charm hadrons and most of the other background sources. The v2 of electrons from beauty hadron decays at midrapidity is found to be positive with a significance of 3.75 σ. The results provide insights into the degree of thermalization of beauty quarks in the medium. A model assuming full thermalization of beauty quarks is strongly disfavored by the measurement at high pT, but is in agreement with the results at low pT. Transport models including substantial interactions of beauty quarks with an expanding strongly interacting medium describe the measurement within uncertainties.